2019
DOI: 10.1002/pmic.201800370
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Serum Lipids and Lipid‐Derived Metabolites to Investigate Breast Cancer Cell Biology

Abstract: The use of cultured cells has been instrumental in studying biochemical, molecular, and cellular processes. The composition of serum that cells are maintained in can have a profound impact on important cellular checkpoints. We have analyzed cell growth and apoptosis in an estrogen receptor positive breast cancer cell line in the presence of serum that have been treated to remove steroids or lipids, as well-described in the literature. We showed that maintaining cells in the presence of charcoal-dextran-treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Highglucose and no-glucose DMEM didn't contain glutamate and fatty acid. Animal serum used in cell culture provides lipids to cells (Brovkovych et al, 2019). In some experiments, we added 1, 5, or 25 mM glucose to these commercially available glucose-free DMEM (Thermo Fisher Scientific, 11966025).…”
Section: Author Contributionsmentioning
confidence: 99%
“…Highglucose and no-glucose DMEM didn't contain glutamate and fatty acid. Animal serum used in cell culture provides lipids to cells (Brovkovych et al, 2019). In some experiments, we added 1, 5, or 25 mM glucose to these commercially available glucose-free DMEM (Thermo Fisher Scientific, 11966025).…”
Section: Author Contributionsmentioning
confidence: 99%
“…4D ). 29 This result suggests the usefulness of A6 as a selective lipase mimetic in more complex physiologically relevant settings.…”
Section: Resultsmentioning
confidence: 88%
“…CerS2 is the predominant CerS expressed in the kidney ( 21 , 30 ), and proteomic analyses of HEK293 cells have revealed that CerS2 is expressed at 10-fold higher levels than CerS5, whereas CerS1, CerS3, CerS4, and CerS6 were either not detected or detected at trace levels ( 31 ). Although some ceramides are present in the fetal bovine serum ( 32 ), and Cer can be generated by hydrolysis of SM or glucosylceramide ( Fig. 1 ), the CerS-mediated pathways are major routes of SL production ( 18 , 19 , 20 , 21 ).…”
Section: Resultsmentioning
confidence: 99%